2004
DOI: 10.1071/ch03221
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation of Ionic Liquids at Elevated Temperatures

Abstract: Ionic liquids based on the imidazolium cation are found to degrade, yielding volatile degradation products, at temperatures significantly lower than previously reported and thus a parameter Tz/x (the maximum operating temperature) is developed to provide a more appropriate estimate of thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
220
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(239 citation statements)
references
References 0 publications
12
220
0
4
Order By: Relevance
“…5e and f) for both the steels. Also the HMImPF 3 (C 2 F 5 ) 3 degraded, in accordance with the observation of Baranyai et al [8], forming a dark, thin and adherent interaction layer ( Fig. 5g and h).…”
Section: Forty-eight Hours Immersion Tests At 220 1csupporting
confidence: 72%
“…5e and f) for both the steels. Also the HMImPF 3 (C 2 F 5 ) 3 degraded, in accordance with the observation of Baranyai et al [8], forming a dark, thin and adherent interaction layer ( Fig. 5g and h).…”
Section: Forty-eight Hours Immersion Tests At 220 1csupporting
confidence: 72%
“…Finally, by replacing the 3-methylimidazolium dication with the 3-benzylimidazolium dication (28)(29)(30) and connecting them by a dodecane linkage chain, the melting points appear higher compared to those of the 3-methylimidazolium series, especially in the case of the bromide salt.…”
Section: High Stability Geminal Dicationic Ionic Liquidsmentioning
confidence: 99%
“…These observations are basically the same as those in the previous reports. 7,10,11 Figures 3 and 4 show the pyrogram of BMImCl at 550˚C by FID and its thermal decomposition pathways, respectively. Five main peaks were also observed in the pyrograms and identified to be chloromethane (4), 1-butene (5), 1-chlorobutane (6), 1-methylimidazole (a) and 1-butylimidazole (c).…”
Section: Py-gc Measuring Conditionsmentioning
confidence: 99%
“…Based on the yields of 1-methyl-and 1-ethylimidazoles, it was concluded that the less nucleophilic nature of TFSA led to much smaller yields of 1-ethylimidazole. 10 More recently, rapid thermolysis up to at 435˚C of EMIm salts with nitride, chloride and bromide anions was studied by FT-IR and time-of-flight MS measurements of the evolved species. 11 As for EMIm halides, the main products were haloalkanes and 1-methyl-and 1-ethylimidazoles.…”
Section: Introductionmentioning
confidence: 99%